Die Trauermücken - Fauna der Bundesrepublik Deutschland (Diptera: Cecidomyiidae). - Menzel, Frank (Contributions to Entomology = Beiträge zur Entomologie, 2000)
Faunistic analyses have produced new information on the distribution and diversity of the Sciaridae in Germany. One result of this has been the preparation of an extensively revised and greatly enlarged check list of the black fungus gnats of Germany, in which all sciarid records from the entire territory of the Federal Republic are included [cut-off date 31 December 1998]. The present work is based on some 141,000 adult gnats from 20 museums and private collections in Germany. Numerous previously unpublished records are included, based on personal faunistic investigations or on the revision of historic collections. Furthermore, samples made available by 56 entomologists from all parts of Germany have been evaluated, and these contained very numerous specimens. - The sciarid fauna of the Federal Republic of Germany now stands at 343 valid species in 24 genera, with 10 ’species incertae sedis’. This up-to-date check list, which is based on the revised nomenclature and more stable classification put forward by Menzel & Mohrig (2000), reflects the current ’state-of-the-art’ of the inventory of species in the Federal Republic of Germany. This publication contains a thoroughly revised and enlarged list of the literature sources. The results presented here have also made it possible to see more precisely how the German sciarid fauna fits into the recent fauna of the Palaearctic region and to make a faunistic comparison with the Sciaridae of certain other European countries. Keywords Diptera, Sciaridae, Germany, biodiversity, faunistics, check list, locality list.